Meta-Analysis: The Effect of Project Based Learning on Science Process Skills - Muhammad Wahyu Setiyadi; A.A.Istri Agung Rai Sudiatmika; Ketut Suma; Nyoman Suardana (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS (JPBN), 2024)
This study aims to examine the effect of the Project-based Learning model on biological science process skills with meta-analysis methods. This research used a method in the form of a meta-analysis. The research population is in the form of scientific articles that have been published in national and international journals about the use of the Project-based learning model that has been published in the last 10 years. The sample used is a project-based learning scientific article on science process skills in biology learning.  Based on the meta-analytical calculations above, it can be concluded that there is a relationship from all articles that measure the influence of the project-based learning model on science process skills, where the p value of < 0.002 means that the analysis is significant with sig. 0.05 and I^2 of 94.508% show that learning using the project-based learning model has a very large influence on science process skills